Relevância de uma cimentação segura em poços de petróleo - Matos, Lucas Moura (Universidade Federal Rural do Semi-Árido, 2019)
Among all the processes and steps that are taken to make a well capable of producing oil, cementing is undoubtedly one of the most important and arduous operations and has a key role in the safety and stability of the well. From this, it is necessary to give greater relevance during the execution of the stages of this operation, and that it is closely monitored following the rules and using techniques and good practices in order to achieve the desired results. Thus, the elaboration of this research was made through a bibliographic study focusing on the relevance of safe cementation in oil wells. Given the researched content it was possible to realize how great is the relevance of this step to the continuation of the other successive steps to this one, and the need to apply practices and techniques in order to reduce the risks of failure and ensure greater safety in extraction operations of hydrocarbons.
Monografia
Keywords: Cimentação; Segurança; Petróleo; Cementation; Safety; Petroleum; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA